Analisis Swot pada Usaha Mikro Kecil dan Menengah (UMKM) : (Studi Kasus pada Warung Bunda Dirga di Kecamatan Cikarang Utara) - Opi Yanti; Daspar Daspar (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
One type of MSME that assists individuals in meeting their basic needs is the grocery store. The presence of small grocery stores greatly strengthens the local economy, especially in rural areas. Conventional grocery stores still survive and make a significant contribution to the local economy, despite the presence of several more contemporary retail companies in recent years. This study aims to evaluate the strategies used by MSME "Warung Bunda Dirga," including social media advertising, digital delivery services, customer service, product selection and styling, and more. Using SWOT analysis, business owners can plan product development, optimize competitive advantages, anticipate emerging threats, and take advantage of market opportunities to increase customer satisfaction, by thoroughly understanding Warung Bunda Dirga's strengths, weaknesses, opportunities, and threats, owners can make strategic decisions that drive the growth and sustainability of the company. It is expected that the strategies used will increase the company's sales and profitability in the long run. For this qualitative study approach, data was collected through direct interviews. In the face of the explosive expansion of minimarkets and the increasing number of competitors, the owner of Warung Bunda Dirga must devise strategies that can maintain customer loyalty and ensure the survival of the company in the long run.